Improved bees algorithm for dynamic economic dispatch considering prohibited operating zones - Sharma, Mahesh Kumar; Phonrattanasak, Prakornchai; Leeprechanon, Nopbhorn (2015 IEEE Innovative Smart Grid Technologies - Asia (ISGT ASIA), 2015)
The proposed improved bees algorithm (IBA) finds a trustworthy solution to the dynamic economic dispatch (DED) problem considering the prohibited operating zones. Additional techniques such as constraint handling, adaptive patch size, and limited search space are integrated with general bees algorithm, making significant improvement in the overall performance of the proposed technique. The DED problem under consideration is performed over the whole dispatch period while satisfying the operational constraints such as transmission losses, ramp rate limits, system load demand, prohibited operating zones, and spinning reserve. Simulations were performed for testing the proposed method for the DED problem with a six-unit system. The results obtained for proposed algorithm are compared with the other candidates, i.e. particle swarm optimization, genetic algorithms, and the general bees algorithm. The results obtained from the distribution and the convergence graph show that the proposed IBA has enough potential to achieve a good quality solution together with the better computational efficiency.